Digital documentation in Africa : evaluation of the offer and uses in the human sciences of the University Cheikh Anta Diop of Dakar - (:unkn) unknown (My University, 2018)
University libraries in French-speaking African countries face a documentary supply challenge in a context of a lack of financial resources, an increase in the cost of documentation, and some inefficient organizational forms. This thesis aims at first, from surveys and collections of diverse data, to establish the state of the paper and digital documentary offer at the University Cheikh Anta Diop of Dakar, in SHS, highlighting points comparison with other Sub-Saharan Francophone Universities. The results are intended to quantify and qualify this offer, to point out new dynamics in the context of digital documentation with different types of actors. In addition, librarians seek to rely fully on Open Access, both in terms of access to resources and the value of local funds. Digital information is increasingly seen as the best way to meet the information needs of the university community at Dakar's Cheikh Anta Diop University (UCAD). Nevertheless, it is often confronted with problems of access to information but also of use of documentary resources. This research focuses, in a second part, to appreciate the uses of digital resources, in a comparative way between several disciplines at UCAD and between teachers and students. Recommendations are made to try to improve the documentary services in this University.
Keywords: African Research